Effect of consumption of I, Se, S and nanoaquacitrates on hematological and biochemical parameters of the organism of rabbits - О. V. Boiko; О. F. Honchar; Y. V. Lesyk; І. І. Kovalchuk; B. V. Gutyj; A. Z. Dychok-Niedzielska (Regulatory Mechanisms in Biosystems, 2021)
Using nanotechnologies to obtain compounds of mineral substances is promising because of the importance of the amount of mineral substances, but the limiting factor is particularly their bioavailability in the digestive tract. The conducted studies determined the stimulating effect of nanoaquachelates of separate biogene microelements on the course of biochemical processes of the organisms of animals, their productivity and quality of the obtained products. However, the mechanisms of impact of carboxylates of separate elements and their combinations on functioning of physiological systems of various species of animals, level of transformation of these elements into the products and their biological value remain unstudied. Therefore, the objectives of the study were changes in hematological biochemical and productive parameters of the organisms of rabbits consuming I, Se, S, the impacts of these elements on their organism from the 53 to 85th days of life. Studies were performed on young Termonde rabbits. Animals of experimental groups I, II, III, and IV were fed with feeds of the diet of the control group for 24 h with water containing solution of І, Se, S calculated respectively as 2.5, 5.0, 10.0 and 20.0 µg of І/L of water. The experiment lasted 45 days, including a 12 day preparation period and 33 day experimental. On the 53rd day of life of animals in the preparation period, and 68th and 85th days of life in the experimental periods (15th and 33rd days of watering with supplements), we collected samples of blood from the marginal ear vein of 6 animals (3 males and 3 females) of the group for hematological and biochemical studies. We determined that watering with the solution of microelements І, Se, S led to changes in the overall amount of white blood cells, making it 17.1% lower in the blood of animals of the experimental group II, 26.2% higher in group ІІІ on the 15th day, and 12.0% higher in group IV on the 31st day of the experiment compared with the control. Absolute amounts of lymphocytes, monocytes and granulocytes by the periods of the study were observed to have no significant changes throughout the study, though their parameters were within the physiological values compared with the control. The amount of red blood cells in the blood of rabbits of experimental groups І, ІІ and ІІІ was higher respectively by 8.1%, 5.7% and 12.0% at the first stage of the study and 18.1%, 13.3%, 24.5% and 24.9% higher in animals of experimental groups І, ІІ; ІІІ and ІV at the final stage of the study compared with the control group. Hemoglobin concentration in blood of rabbits of experimental groups II and III during the study was significantly higher. Hematocrit value in blood of rabbits of experimental groups I–III was significantly higher on the 33rd day of the experiment compared with the control. Consumption of solution of microelements in the amount of 10.0 µg of I/L by the animals of experimental group III led to 15.1% higher content of total protein in the blood on the 33rd day of the study compared with the control group of animals. The level of creatinine was no higher than the physiological parameters and was 9.2%, 15.0% and 15.4% higher in the blood of rabbits of experimental groups II, III, IV on the 33rd day of the experiment compared with the control group. No significant changes in the content of triacylglycerols in the blood of rabbits of the experimental groups were seen throughout the study. However, the content of cholesterol in the blood of rabbits of experimental groups III and IV was significantly higher at the first stage compared with the control group. Further, it is practical to study physiologically substantiated amounts of solution of microelements І, Se, S in the diet of mother rabbits to determine their effect on their ability to become pregnant, reproductive function, milk production and survival of offspring.